SEED VIABILITY TEST OF COMMERSIAL DATES ON THE MARKET - Ekosari Roektiningroem; Purwanti Widhy (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
This research aims to to know the seed viability of the two dates on the market. It has been done from July to November 2014, in the laboratory of Mathematics and Natural Science Faculty, Yogyakarta State University. The type of Dates seeds are Sayer (oval-cilindrical, ±3cm, dark orange brown/more light than another), and Lulu (round, ±2cm, dark maroon reddish /more dark than Sayer’s). Viability test by germination testing; conducted on plastic tray with cotton sheet and fabric covered; fill with 100 grains of seeds. Repeated 4 times. Incubation at room temperature (±30oC). The parameters were seed fresh weight, seed dry weight, seed moisture, germination percentage and germination rate. The results were analyzed by compare mean - independent samples t test of SPSS 18’th. The results showed that the viability of both of Date’s seeds from local’s market (Sayer and Lulu) is high. Sayer’s have better viability than Lulu’s (due to the germination percentage and germination rate). Keywords: date seed, viability test, germination test